2007
DOI: 10.1016/j.pharmthera.2006.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of monocyte and macrophage function by adenosine receptors

Abstract: Adenosine is an endogenous purine nucleoside that, following its release into the extracellular space, binds to specific adenosine receptors expressed on the cell surface. Adenosine appears in the extracellular space under metabolically stressful conditions, which are associated with ischemia, inflammation, and cell damage. There are 4 types of adenosine receptors (A 1 , A 2A , A 2B and A 3 ) and all adenosine receptors are members of the G protein-coupled family of receptors. Adenosine receptors are expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
154
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(165 citation statements)
references
References 124 publications
6
154
0
1
Order By: Relevance
“…The rather marginal effect seen with CO and bilirubin in our experiments may open a further possibility that HO-1 translocates to the nucleus to bind to a transcription factor or a protein complex, resulting in enhanced transcription of Adora A 2A (Lin et al, 2007). Adora A 2A agonists are capable of not only blocking the inflammatory potential of human macrophages, such as pathogenstimulated NO, TNF-␣, or IL-12 production (Hasko et al, 2007) but also promoting wound healing in disease states such as diabetes (Montesinos et al, 1997).…”
Section: Discussionmentioning
confidence: 64%
“…The rather marginal effect seen with CO and bilirubin in our experiments may open a further possibility that HO-1 translocates to the nucleus to bind to a transcription factor or a protein complex, resulting in enhanced transcription of Adora A 2A (Lin et al, 2007). Adora A 2A agonists are capable of not only blocking the inflammatory potential of human macrophages, such as pathogenstimulated NO, TNF-␣, or IL-12 production (Hasko et al, 2007) but also promoting wound healing in disease states such as diabetes (Montesinos et al, 1997).…”
Section: Discussionmentioning
confidence: 64%
“…ADORA2A is a potent regulator of macrophage functions, including Fc receptor-mediated phagocytosis and pattern recognition receptor-mediated cytokine production. 39 Detailed studies are in progress in our laboratory to clarify the molecular mechanism and general implication of cytokine induction in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that the hydrolysis of ATP may be pivotal in regulating the immunoregulatory phenotype of M-CSF-macrophages. As macrophages express adenosine receptors and that adenosine receptor stimulation regulates IL-10 secretion, 51 we addressed the role of adenosine generated following ATP hydrolysis on the cellular fate of macrophages by using adenosine deaminase (ADA) that degrades adenosine, and caffeine that inhibits adenosine receptor. Results showed that inhibition of adenosine receptor during M-CSF-macrophages activation inhibits IL-10 secretion (Fig.…”
Section: Cd39 Is Involved In the Acquisition Of The Immunoregulatory mentioning
confidence: 99%